Strategi Pengembangan Usaha Peternakan dan Pengolahan Susu Kambing di Goatzilla Farm - Anang Febri Prasetyo; Nurkholis Nurkholis (Politeknik Negeri Jember, 2018)
This study aimed to analyze the development strategy of business and goat milk processing in the Goatzilla Farm, Lumajang, East Java. This research was descriptive. Methods of data by surveys using questionnaires. Data were analyzed by SWOT matrix to find out opportunities and threats in Goatzilla Farm. The results of the study used SWOT analysis. Alternative strategies recommendated in the Goatzilla Farm were SO strategies (Strength Opportunities), namely comparative strategy primacy, efficiency and internal development, and information technology to improve product quality. The results of the study showed to need cooperation with the government, farmers, and distribution networks to provide raw materials and increased product sales. The threat of Goatzilla Farm needed to watch out for was licensing which was processed immediately to support a bargaining position. There was no sufficient licensing, it could threat the sustainability of the business.Â